2022
DOI: 10.3389/feduc.2022.831619
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Geography Learning on Students’ Emotions and Motivation in Immersive Virtual Reality

Abstract: This paper assesses the impact of emotional arousal on learning through a virtual reality video of geography immersion learning. Validity was measured with traditional questionnaire data and using electroencephalography (EEG). Twenty-four human subjects were recruited and presented with eight geography immersive learning videos with different affective tendencies. EEG data of the subjects were collected while they were watching the videos. After the video watching, subjects were requested to fill in an emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…This can make the learning process more enjoyable and memorable, leading to better retention of information and skills. An immersive virtual reality-based learning environment can not only improve student engagement and motivation but also promote positive emotions, and thus contributing to teacher effectiveness with more interactive learning experience [24]. Moreover, studies [25], [26], [27] reported significant improvements in students' learning outcomes in immersive classrooms with virtual and augmented reality.…”
Section: Discussionmentioning
confidence: 98%
“…This can make the learning process more enjoyable and memorable, leading to better retention of information and skills. An immersive virtual reality-based learning environment can not only improve student engagement and motivation but also promote positive emotions, and thus contributing to teacher effectiveness with more interactive learning experience [24]. Moreover, studies [25], [26], [27] reported significant improvements in students' learning outcomes in immersive classrooms with virtual and augmented reality.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported a positive effect on learning through the use of immersive technologies that emulate the manufacturing processes in educational contexts [8][9][10][11]. Other studies have also found positive results in learners' mood and motivation when utilizing virtual reality (VR) [12][13][14]. For instance, Su et al [15] conducted an experiment to investigate whether VR immersive technology enhances mathematics geometry learning and motivation.…”
Section: Related Work 21 Virtual Tours For Education and Trainingmentioning
confidence: 99%
“…To cultivate students' practical innovation, self-learning ability, and exploratory spirit, immersive learning based on virtual reality can drive a transformation in teaching methods and enhance the quality of biology education.Virtual reality technology is utilized to recreate experimental facilities and environments or provide immersive experiences of tangible biological phenomena, holding immense potential for applications in biology education [1][2]. Relevant studies indicate that virtual biology learning environments created through virtual reality technology have an overall positive impact on students' cognition, skills, and learning motivation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%